Development of sustainable high performance geopolymer concrete and mortar using agricultural biomass—A strength performance and sustainability analysis - Nagaraju, T. Vamsi; Bahrami, Alireza; Azab, Marc; Naskar, Susmita (Frontiers in Materials, 2023)
The environmentally friendly alternative to conventional Portland cement concrete is geopolymer concrete. In addition, rising carbon taxes on carbon emissions and energy-intensive materials like cement and lime impact the cost of industrial by-products due to their pozzolanic nature. This research evaluates the compressive strength and flexural strength of geopolymer concrete, and the compressive strength of geopolymer mortar. Geopolymer mortar data were used for strength assessment using an analytical approach, and geopolymer concrete data were utilized for strength and sustainability performance. Using artificial neural networks (ANN), multi-linear regression (MPR) analysis, and swarm-assisted linear regression compressive strength models were created based on experimental datasets of geopolymer mortar mixes with variable precursors, alkali-activator percentages, Si/Al, and Na/Al ratios. The strength and sustainability performances of geopolymer concrete blends with various precursors were assessed by considering cost-efficiency, energy efficiency, and eco-efficiency. The work's originality comes from enhancing sustainable high-performance concrete without overestimating or underestimating precursors. Extensive experimental work was done in the current study to determine the best mix of geopolymer concrete by varying silica fume, ground granulated blast furnace slag (GGBS), and rice husk ash (RHA). A scanning electron microscopic study was conducted to understand the geopolymer matrix's microstructure further. A comprehensive discussion section is presented to explain the potential role of RHA. The replacement of conventional concrete in all its current uses may be made possible by this sustainable high-performance concrete made with RHA.